FROM DARKNESS INTO LIGHT: KYAI SOLEH DARAT’S CONTRIBUTION TO THE FORMATION OF KARTINI’S ISLAMIC THOUGHT - Sumiati, Wina (JEJAK : Jurnal Pendidikan Sejarah & Sejarah, 2025)
Kiai Soleh Darat was an Indonesian scholar who had a significant influence on the transformation of Kartini’s thinking. Through his teachings on the interpretation of the Qur’an, Kartini became increasingly interested in understanding its contents, which had long been considered taboo to translate by society before the 20th century and was prohibited by the Dutch colonial government. The purpose of this study is to analyze the influence of Kiai Soleh Darat on Kartini’s views if Islam. The method used to analyze this issue is a qualitative approach by collecting the necessary data through literature study. Kartini’s letters to her colleagues in the Netherlands serve as concrete evidence of how her thoughts transformed after learning Islam from Kiai Soleh Darat. The findings show that Kartini, who was initially disappointed with the Javanese community’s reluctance to understand the contents of the Qur’an, became increasingly open-minded in her effort to comprehend and embrace Islam as her religion.